Perceptions of thalassemia and its treatment among Malaysian thalassemia patients: A qualitative study - Ismail, Wan Ismahanisa; Ahmad Hassali, Mohamed Azmi; Farooqui, Maryam; Saleem, Fahad; Aljadhey, Hisham (Australasian Medical Journal, 2016)
Background Thalassemia is a common public health problem in Malaysia and one of the most common chronic and genetic disorders. Aims The present qualitative study explores knowledge about thalassemia, perceptions about conventional therapies and the points that affect Malaysian patients with thalassemia in taking medications correctly. Methods This study used a qualitative method. Purposive and theoretical samplings were combined to explore the issues related to thalassaemia and its perceptions. Twenty-one patients with thalassemia were recruited from the Thalassemia Society, Kedah, Malaysia from July to October 2015. The semi-structured interviews were audio taped, transcribed verbatim and translated into English for thematic content analysis. Results Participants perceived thalassemia as an incurable disease which is due to genetic and blood related disorders. A positive perception was shown towards conventional therapies considering it as effective for their condition. High treatment cost was given as a reason why patients perceived conventional therapies as effective. Fear of side effects was the main reason the patients gave for their delay in looking for treatment. However, due to limited treatment options, patients were reported to show positive attitude towards the side effects due to thalassemia treatment. Conclusion This explanatory investigation suggests that thalassemia patients’ understanding about thalassemia is complex in nature. The findings may help healthcare providers remove myths about the fear of the treatment. It may also help in improving patient’s compliance towards the thalassemia therapies. Main focus for future research should be on those patients who declined the conventional therapies.